Too much of a good thing? Absorptive capacity, firm performance, and the moderating role of entrepreneurial orientation. (23rd October 2012) - Wales, William J.; Parida, Vinit; Patel, Pankaj C.
<x xml:space="preserve">Abstract</x> Absorptive capacity (ACAP) refers to a firm's ability to acquire, assimilate, transform, and exploit new knowledge. Research has yet to acknowledge the possibility of limits to the financial returns of this important strategic construct. This study suggests an inverted‐U shaped relationship between ACAP and financial performance. Based on data from 285 technology‐based small and medium enterprises, we observe gains within three prospective, secondary measures of growth to diminish beyond lower levels of ACAP, even turning negative and becoming harmful beyond intermediate levels. We find that entrepreneurial orientation (EO) moderates the ACAP‐performance relationship, enhancing financial gains at lower levels of ACAP and mitigating the decline in financial performance at higher levels of ACAP. Further, with higher EO, higher ACAP can be achieved before financial returns diminish.Copyright © 2012 John Wiley & Sons, Ltd.